DIGITAL TRANSFORMATION COMPETITIVE ADVANTAGE OF MSMES THROUGH E-COMMERCE IN INDONESIA: A CONCEPTUAL STUDY - Wulandari, Riska; Kristina, Ni Made Rai; Widiari, Putu Ayu Ossi; Premananda, Luh Putu Uttari; Krisdayanthi, Astrid; Wirawan, I Komang Adi Satrya (International Journal of Social Studies, 2025)
This study examines how digital transformation through e-commerce can be a competitive advantage for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Based on literature studies and secondary data from 2020–2025, the results indicate that e-commerce plays a key role in expanding markets, increasing efficiency, and strengthening brand image. However, challenges such as low digital literacy, infrastructure inequality, and cybersecurity risks remain. The success of digital transformation is influenced by internal readiness, managerial support, and collaboration with digital platforms. Using the Technology-Organization-Environment (TOE) framework and Dynamic Capability Theory, this study concludes that inclusive and adaptive digital transformation, accompanied by policy support and cross-sector collaboration, is crucial for realizing a resilient and competitive Indonesian digital economy.